Burden of arrhythmias in patients with obstructive sleep apnea and its impact on mortality: a descriptive study from the National Inpatient Sample. (14th October 2021) - Gopalakrishnan, A; Dhulipala, V; Grillo, M; Ayala-Rodriguez, C; Garyali, S; Reddy, S
Abstract: Background: Obstructive sleep apnea (OSA) accounts for significant mortality and morbidity worldwide. A limited but emerging literature has revealed increased risk of sudden cardiac death in patients with OSA. There is paucity of data on arrhythmia burden in patients with OSA, particularly in hospitalized patients. Purpose: Therefore, we sought to study the prevalence of atrial and ventricular arrhythmias among hospitalized patients with OSA and examine its impact on sudden cardiac death and in-hospital mortality. Methods: All patients over 18 years of age with OSA were extracted from the National Inpatient Sample (NIS) from 2009–10 using 9th revision of International Classification of Diseases (ICD-9) code 327.23. Demographic data, hospital characteristics, comorbid conditions, and arrhythmia burden including different types of arrhythmia were identified. Clinical outcomes were in-hospital mortality, length of stay and sudden cardiac death. Logistic regression analysis was performed to determine the impact of arrhythmia on in-hospital mortality in patients with OSA. Hospital level discharge weights provided by NIS were used to obtain national estimates of OSA hospitalizations. Results: OSA was prevalent in 2.8% (n=1, 114, 297) of all hospitalizations among which 20.1% had any arrhythmia (n=223, 974). Patients with arrhythmia were older, more likely to be males, and had higher prevalence of risk factors and comorbid conditions except for chronic liver disease, and smoking (p<0.0001 for all). Arrhythmia burden analysis revealed increase prevalence of both atrial and ventricular arrhythmia in patients with OSA compared to general population. In-hospital mortality (3.48% vs 1.27%; p<0.0001), length of hospital stay (6.4±0.1 vs 5±0.1; p<0.001) and sudden cardiac death (1.34% vs 0.4%; p<0.0001) were higher in OSA patients with arrhythmia compared to OSA patients without arrhythmia. Presence of arrhythmia in OSA patients was associated with increased in-hospital mortality in both unadjusted [OR 2.79 (2.62–2.98); p<0.001] and multivariable model adjusted for all risk factors and comorbid conditions [OR 1.83 (1.69–1.98); p<0.001]. Conclusion: Arrhythmia burden was higher in patients with OSA compared to the general population. Presence of arrhythmia among OSA patients was independently associated with increased in-hospital mortality and longer hospital stays. Routine evaluation to assess arrhythmia burden in patients in OSA could be a potential target to decrease sudden cardiac death in this high risk population. FUNDunding Acknowledgement: Type of funding sources: None.